Mentha aquatica L. extract affects mitochondrial bioenergetics - Ferreira, Fernanda M. (2013)
Mentha aquatica extracts are commonly used in food flavoring and pharmacology. In the present work, we evaluated the possible effects of Mentha aquatica L. (water mint) ethanolic extract on rat liver mitochondria bioenergetics. Rat liver mitochondria were isolated using conventional protocols. M. aquatica extracts were evaluated on mitochondrial membrane electric potential by using a tetraphenylphosphonium cation (TPP+)-selective electrode, while mitochondrial respiratory activity was evaluated using a Clark-type oxygen electrode, either in the presence of glutamate + malate and succinate as respiratory substrates. Mitochondrial osmotic volume changes were measured by the pseudo-absorbance changes at 520 nm with a suitable spectrophotometer- recorder set up. Incubation of M. aquatica extracts with isolated liver mitochondria resulted in a decrease in mitochondrial oxidative phsophorylation, reflected both by a decrease in respiratory parameters (state 3, respiratory control ratio -RCR, uncoupled respiration) and in membrane electric potential. This decrease can probably be related with the polyphenolic composition of the extract (mainly eriodictyol-7-O-rutinoside, luteolin-7-O-rutinoside, naringenin-7-O-rutinoside, hesperitin-7-O-rutinoside and rosmarinic acid), that can interact with membrane and change the inner mitochondrial membrane characteristics. Nevertheless, for the range of concentrations tested (up to 25 ug mg protein _1) no significant increase in the inner mitochondrial membrane permeability was observed. Although decreasing the RCR, the M. aquatica extract did not affect the mitochondrial phosphorylative capacity, as estimated by the P/O ratio. Nevertheless, for highest concentrations (25 ug mg protein _1 or higher) the inhibitory effect over mitochondrial respiratory chain (as reflected by uncoupled respiration) shows hindrance of mitochondrial respiratory maximal capacity. Overall, the present study suggests that the consumption of M. aquatica leaves ethanolic extract should be regarded as hazardous, specially concerning high daily dosages.